Spinal Anesthesia with Targeted Sedation based on Bispectral Index Values Compared with General Anesthesia with Masked Bispectral Index Values to Reduce Delirium: The SHARP Randomized Controlled Trial. (19th October 2021) - Brown, Charles H.; Edwards, Charles; Lin, Charles; Jones, Emily Ledford; Yanek, Lisa R.; Esmaili, Melody; Gorashi, Yara; Skelton, Richard; Kaganov, Daniel; Curto, Ryan; Lessing, Noah L.; Cha, Stephanie; et al.
Abstract : Background: Reducing depth of anesthesia and anesthetic exposure may help prevent delirium, but trials have been conflicting. Most studies were conducted under general anesthesia or in cognitively impaired patients. It is unclear whether reducing depth of anesthesia beyond levels consistent with general anesthesia reduces delirium in cognitively intact patients. The authors' objective was to determine whether a bundled approach to reduce anesthetic agent exposure as determined by Bispectral Index (BIS) values (spinal anesthesia with targeted sedation based on BIS values) compared with general anesthesia (masked BIS) reduces delirium. Methods: Important eligibility criteria for this parallel-arm randomized trial were patients 65 yr or greater undergoing lumbar spine fusion. The intervention group received spinal anesthesia with targeted sedation to BIS greater than 60 to 70. The control group received general anesthesia (masked BIS). The primary outcome was delirium using the Confusion Assessment Method daily through postoperative day 3, with blinded assessment. Results: The median age of 217 patients in the analysis was 72 (interquartile range, 69 to 77). The median BIS value in the spinal anesthesia with targeted sedation based on BIS values group was 62 (interquartile range, 53 to 70) and in the general anesthesia with masked BIS values group was 45 (interquartile range, 41 to 50; P < 0.001). Incident delirium was not different in the spinal anesthesia with targeted sedation based on BIS values group (25.2% [28 of 111] vs . the general anesthesia with masked BIS values group (18.9% [20 of 106]; P = 0.259; relative risk, 1.22 [95% CI, 0.85 to 1.76]). In prespecified subgroup analyses, the effect of anesthetic strategy differed according to the Mini-Mental State Examination, but not the Charlson Comorbidity Index or age. Two strokes occurred among patients receiving spinal anesthesia and one death among patients receiving general anesthesia. Conclusions: Spinal anesthesia with targeted sedation based on BIS values compared with general anesthesia with masked BIS values did not reduce delirium after lumbar fusion. Abstract : This prospective single-center trial randomized patients undergoing spine surgery to spinal anesthesia with targeted sedation to Bispectral Index greater than 60 to 70 versus general anesthesia without Bispectral Index guidance. There was no difference in the incidence of postoperative delirium between randomized groups in the trial. Future studies are needed to determine whether these findings can be replicated at other centers and whether the results differ by cognitive status. Supplemental Digital Content is available in the text.